Between Emphasis and Exaggeration: Verbal Emphasis in the English of Cape Breton Island - Falk, Lilian (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
The paper examines a variety of stylistic features used by Cape Breton speakers to emphasize a point. Among the most frequently used, we see syntactic extraposition, rhetorical openings and closings, as well as the repetition of key words and the linking of synonyms. Aside from these features, we see also the use of rhetorical superlatives and proverbial comparisons, as well as a number of rhetorical interjections. On the basis of the examples examined here, the paper tries to describe the various functions of these features in narrative segments. The analysis suggests that while some of the expressions may be specific to Cape Breton, their function in discourse follows patterns similar to those which have been observed in Standard English.